2003
DOI: 10.1002/gcc.10177
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of ALK to the Ran‐binding protein 2 (RANBP2) gene in inflammatory myofibroblastic tumor

Abstract: Inflammatory myofibroblastic tumor (IMT) is a rare mesenchymal proliferation of transformed myofibroblasts, with a prominent inflammatory cell component, that can mimic other spindle cell processes such as nodular fasciitis, desmoid tumor, and gastrointestinal stromal tumor. Genetic analyses have recently demonstrated rearrangements of anaplastic lymphoma kinase (ALK), located at 2p23, in a subset of IMTs. Molecular characterizations have identified ALK fusions involving tropomyosin-3 and -4 (TPM-3 and -4), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
167
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(176 citation statements)
references
References 24 publications
6
167
0
2
Order By: Relevance
“…11 Subsequently, recurrent ALK chimeric oncogenes involving diverse partner genes (RanBP2, CLTC, CARS, and others) were identified in inflammatory myofibroblastic tumors. [15][16][17][18] More recently, the ALK gene has been shown to be involved in small subsets of epithelial malignancies, including carcinomas of pulmonary, esophageal, mammary gland, and gastrointestinal origin. [19][20][21][22] To the best of our knowledge, this is the first report of a recurrent ALK locus rearrangement in a primary kidney tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Subsequently, recurrent ALK chimeric oncogenes involving diverse partner genes (RanBP2, CLTC, CARS, and others) were identified in inflammatory myofibroblastic tumors. [15][16][17][18] More recently, the ALK gene has been shown to be involved in small subsets of epithelial malignancies, including carcinomas of pulmonary, esophageal, mammary gland, and gastrointestinal origin. [19][20][21][22] To the best of our knowledge, this is the first report of a recurrent ALK locus rearrangement in a primary kidney tumor.…”
Section: Discussionmentioning
confidence: 99%
“…11 Subsequently, ALK rearrangements were found in several phenotypically different hematologic neoplasms [12][13][14] and in histogenetically unrelated inflammatory myofibroblastic tumor. [15][16][17][18] Recently, ALK rearrangements and EML4-ALK and KIF5B-ALK fusions were discovered in a subset of non-small cell lung carcinomas; 19,20 proteomics reports suggested a possible TPM4-ALK fusion in esophageal carcinoma; 21,22 and an exon array profiling study demonstrated the EML4-ALK fusion in 2.5% of breast and colon cancers. 23 ALK is also activated in B5 to 35% of neuroblastomas and neuroblastoma cell lines by a different mechanism involving point mutations and/or gene locus amplifications.…”
mentioning
confidence: 99%
“…4,5,7,9,[20][21][22][23][24][25][29][30][31][32] Cytogenetic and molecular analyses have demonstrated a number of ALK fusion gene partners, including RANBP2-ALK, TPM3-ALK, TPM4-ALK, CLTCALK, CARS-ALK and SEC31L1-ALK. 5,9,21,25,29,31 In the present study, ALK rearrangements were identified in 14 of 21 cases of inflammatory myofibroblastic tumor of the urinary bladder. These findings are similar to recent studies that identified ALK rearrangements by FISH in a few series of urinary bladder inflammatory myofibroblastic tumors.…”
Section: Utility Of Alk-1 Protein Expressionmentioning
confidence: 99%
“…Rearrangements of ALK with various gene partners have been identified in inflammatory myofibroblastic tumor from a number of anatomic sites. [20][21][22][23][24] Each rearrangement is believed to result in the creation of novel gene fusions and subsequently leads to aberrant ALK activation. In the urinary bladder, a few series and case studies have reported cases of inflammatory myofibroblastic tumor exhibiting ALK rearrangements.…”
mentioning
confidence: 99%
“…In 1999, Griffin and co-workers demonstrated that such 2p23-rearrangements target the ALK locus and result in the creation of various fusion genes containing the catalytic domain of ALK. 5 So far, 6 ALK fusion partners have been described in IMTs: ATIC (at 2q35), CARS (at 11p15), CLTC (at 17q23), RANBP2 (at 2q13), TMP3 (at 1p23) and TMP4 (at 19p13) 2,[6][7][8][9][10][11][12] Immunohistostochemical studies have detected ALK expression in 40-60% of IMTs. 11,12 In the present study, we describe the cytogenetic and molecular characterization of an IMT with a novel fusion gene, SEC31L1/ALK.…”
mentioning
confidence: 99%